EFEK NAUNGAN DAN CEKAMAN AIR TERHADAP PERTUMBUHAN DAN HASIL KUNYIT DI KISMANTORO, WONOGIRI - Ratri, Anindita Dwi Yogi Sapta; Pujiasmanto, Bambang; Yunus, Ahmad (Universitas Sebelas Maret, 2015)
Turmeric is a medicinal plant that has largest secondary metabolites (curcumin). Improving secondary metabolites with abiotic stress that the provision of shade and water stress. This research aims to study the effects of shade and water stress on growth and yield of turmeric and content of secondary metabolites. The study uses a nested design with two factors, namely shade (without shade, 25%, 50%, 75%) and water stress (without stress, 25% field capacity, 50% field capacity, 25% field capacity). Analysis using the F test and DMRT 5% level. The results showed that shade did not effect to fresh and dry weight of plant. 75% shade decrease root lenght, fresh and dry weight of rhizome. Water stress did not effect to growth and yield of turmeric. The highest curcumin results in conditions without shade and without stress.